Affective, parochial or innovative? Aleppo traders on the margin of global capitalism - Annika Rabo (Revue des Mondes Musulmans et de la Méditerranée)
This article scrutinizes three different, and possible, ways to depict traders in contemporary Aleppo. They can be seen as sharing a distinct culture, as representatives of the petite bourgeoisie, or as examples of entrepreneurs. While all these approaches tell us something about the Aleppo traders, these approaches have great limitations, not least since the latter two – each in its own way – are utility-oriented. It is, I will rather argue, important to analyze Aleppo traders as affective, parochial and innovative, at the same time. Although Aleppo traders find themselves on the margins of global capitalism, they can, in fact, be studied in order to understand salient features of the contemporary world. We have a new affective economy where personalities, emotions and sensibilities are put on the market. The article is based on material collected during social anthropological fieldwork in Aleppo between 1997 and 2003, but mainly carried out in 1998-1999.